Diagnosing evaporative fraction over land from boundary‐layer clouds. Issue 15 (2nd August 2013) - Gentine, Pierre; Ferguson, Craig R.; Holtslag, Albert A. M.
Abstract: [1] The potential use of continental fair‐weather shallow cumuli as a way to retrieve the daily surface evaporative fraction over land is evaluated in convective conditions. The proposed method utilizes the fact that both the timing of cloud occurrence and the cloud‐base height at the time of occurrence provide strong constraints on the surface energy balance and evaporative fraction. The retrieval is especially reliable in the presence of relatively stable and humid‐free troposphere profiles. The advantage of the method is that it provides a more direct estimate of the surface evaporative fraction than indirect estimation based on inversion of a highly parameterized land‐surface model. In addition, the evaporative fraction is obtained at a scale of a few kilometers, which is more pertinent for weather and climate studies. The retrieval strategy is tested and validated for three contrasting climates: the U.S. southern Great Plains, West Africa, and the Netherlands. We suggest that the use of satellite observations of shallow cumuli can help constrain the retrieval of the surface evaporative fraction within a data assimilation scheme/reanalysis. Key Points: Onset of cumulus provides indicator of evaporative fraction. Cumulus are direct observables of surface energy partitioning Strategy requires less parameterization than inversion of land surface model.